2019
DOI: 10.3390/su11226388
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Public Procurement: From Law to Practice

Abstract: This study aims to propose actions to improve the implementation of sustainable public procurement by identifying the problems perceived by public servants and social economy entities. Two types of questionnaires were sent to organizations in Spain and Europe and 217 complete answers were received (152 from the public sector and 65 from the social entities). In addition, 20 semi-structured personal interviews were conducted by phone with managers of social enterprises and four interviews, also by phone, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
2
10
0
1
Order By: Relevance
“…They were basing procurement decisions on price instead of whole-life costs for over 25 years. A recent study confirms that this tradition has not changed in Europe, as procurers were still associating lower price with best bid (Jiménez et al , 2019). Not just in Europe, China too faced similar resistance from its procurers.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…They were basing procurement decisions on price instead of whole-life costs for over 25 years. A recent study confirms that this tradition has not changed in Europe, as procurers were still associating lower price with best bid (Jiménez et al , 2019). Not just in Europe, China too faced similar resistance from its procurers.…”
Section: Resultsmentioning
confidence: 87%
“…Without the knowledge, procurers in Northern Ireland found it challenging to justify the procurement of often higher cost green products (Erridge and Hennigan, 2012). Government employees in Pakistan (Zaidi et al , 2018), Russia (Romodina and Silin, 2016), China (Zhu et al , 2013) and Europe (Jiménez et al , 2019) were found to be incompetent to implement GGP due to the lack of know-how. In Brazil, lack of know-how was the fourth top barrier identified among a list of 32 barriers (Da Costa and Da Motta, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The mentioned values that the social economy holds are deeply linked with human, sustainable, and social development [2][3][4][5][6][7]. The new Spanish Law 9/2017, from November 8, on Public Sector Procurement includes social and environmental criteria in the award [8,9]. Social economy entities have values and principles that correspond to social, environmental, and ethical criteria, which can be included in public procurement documents.…”
Section: Introductionmentioning
confidence: 99%
“…: 0213-8093 Nº101/2021, pp. 33-56 de las ratios a partir del valor social integrado (San-Jose et al, 2020), los que analizan su componente ético (Zicari, 2020) o aquellos que lo aplican a la compra pública (Bernal et al, 2019;Mendoza et al, 2019). Sin embargo, previamente no ha sido trabajado en el ámbito de la valoración de empresas, pero sin duda, y, sobre todo, para las ENLs tiene gran utilidad por poderse utilizar con objeto de los planes estratégicos o poder hacer un balance de su situación, entre otros.…”
Section: Concepto De Valor Social Integrado Dentro De La Contabilidadunclassified